Sociocultural and linguistic aspects of advertising in Kazakhstan (Eurasian Journal of Philology Science and Education, 2021)
The article looks at sociocultural and linguistic features of advertising, since advertising as a form of communication reflects culture, traditions, changes in the society, sociocultural norms of behavior, standards of life and the level of economic situation of the country. The paper studies the cultural elements of advertising in Kazakhstan from the angle of the theory of Cultural Dimensions by Geert Hofstede and Value Theory by social psychologist Shalom Schwartz. People perceive the world through the prism of cultural values that play a crucial role in marketing and trigger consumer response. Cultural values are a significant factor of a consumer response to marketing stimuli, since each society possesses a set of values and priorities. Following on from this, achieving the desired behavior of consumers involves knowledge of the cultural values and the ability to use them. Socio-cultural analysis shows that cultural values in Kazakhstan combine elements of western and eastern cultures, which is due to its geographical location, resource potential and the development of international relations. Linguistic analysis of the language of advertising reveals the interaction of linguistic and intercultural aspects: the words of the Kazakh language are found in the text of advertising in Russian and vice versa; borrowings in advertising in the Kazakh language take a special place since advertising quickly responds to innovative processes and changes in different areas of life.